Identification of Differentially Expressed Protein from Electrical Stunning of Broiler Chickens Meat Protein - Sandra Hermanto; Maya Ina Sholaikah; Sri Suci Mulyani (Universitas Jenderal Soedirman, 2016)
Identification of differentially expressed protein from the muscle tissue of broiler chicken meat with different conditions of pre-slaughter has been done. Each sample (6 broilers aged 21 days, 1 kg of weight ) was prepared through the process of pre-slaughter with 3 conditions, the first sample slaughtered in a conventional way which untreated electrical stunning, while the second and third sample of the chicken was prepared by using electrical stunning with 1 A and 25 Volts for 5 seconds and 1 A, 125 Volts for 30 seconds. Two biological replicate were done for each of samples. Muscle tissue protein extracted in Tris HCl pH 8.0 and the proteins separation by using SDS-PAGE (Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis). Identification of differentially expressed protein performed by densitometry to identify the profile of the resulting proteins. The results of this study showed that the protein bands constructed in the range of 8.5-140 kDa and 9 dominant protein bands with different relative intensities. Densitogram analysis results showed there are two specific protein bands appear on the results of the electrical stunning which more extensive over expression. This indicates the electrical stunning of slaughter process may triggered the expression levels of certain proteins that do not occur in the nonelectrical stunning.